International Trade Union Seminar on Active Manpower Policy : Vienna, September 17-20, 1963 : Final Report. - Organisation for Economic Co-operation and Development. Social Affairs Division (Paris: OECD, 1964)
This seminar provided for exchange of current experiences and views on active manpower policy by management and trade unionists in the member countries of the Organization for Economic Cooperation and Development. The present volume consists of a report of the proceedings, the conclusions reached by the participants, and reprints of the three background reports prepared for the seminar. The papers and discussion provide an intimate appraisal of important aspects of manpower policies and activities within the member countries. The backgrounds reports were: "Economic and Social Implications of an Active Manpower Policy" by E. Wight Bakke, "Comparison of National Manpower Policies" by Franz Lenert, and "The Trade Union Attitude Towards an Active Manpower Policy" by Herman Beermann. (CH)
Microfiche.
Keywords: Full employment policies; Employment stabilization